Occurrence of hopea Parviflora in Hanovar Range, Western Division, Kanara, Bombay Province-II - Dhareshwar, S. S. (Indian Forester, 1946)
Several experiments of regeneration of Hopea parviflora undertaken have been described with the result achieved in each case. Experiment I is in connection with shelterwood regeneration meothod and this has succeeded well. Experiment II relates to interplanting in teak plantations of varying ages. This experiment failed to show satisfactory results. Experiment III describes planting below 2 years old junglewood regrowth in felled coupes. This has succeeded admirably. Experiment IV shows the result of transplanting in bare lateritic soil. This is also encouraging. Germination of seed in shaded nurseries was not satisfactory perhaps owing to the loss of time in tbe transit of the seed. About three months old transplants succeed better than older seedlings. The writer advocates the method of treatment as described in Experiment for promoting natural regeneration and transplanting under nurse crop as described in Experiment III for artificial regeneration of tne species.